On the commute travel pattern with compressed work schedule - Su, Qida (2022)
Compressed work schedule (CW) is one of the widely known flexible work hours arrangements (FWAs). In the literature, it has been clearly demonstrated that CW can significantly reduce commuting trips per pay period and thereby relieve peak hour congestion. Without policy intervention, how many firms will choose CW? Is it socially beneficial to encourage all commuters to switch to CW? This paper mainly addresses these questions. A bi-level economic model encapsulating employers’ and employees’ choices on their work schedule is then developed. Firstly, the short-run daily and periodic commute patterns of employees are investigated in a modified activity-based bottleneck model. On top of that, the effects of CW on firms’ productivity are incorporated into our long-run analysis. At long-run equilibrium, no employers and employees can benefit by unilaterally switching their schedule type or changing their schedule design. Multiple equilibria are found with the different number of CW users, depending on the agglomeration rate of productivity and the initial status. The social optimums to maximize total net utility are also determined. At a low rate of agglomeration, it is socially beneficial to introduce CW and the system can achieve the social optimum naturally at long-run equilibrium with positive CW users, under mild assumptions. However, when the agglomeration rate is high, the social optimum is no longer achieved, and workers would stick to the normal schedule at equilibrium if the initial case without CW is considered. This can partially explain why CW is not commonly adopted in practice.